2006
DOI: 10.1182/blood-2006-02-002139
|View full text |Cite
|
Sign up to set email alerts
|

Apical sorting of ADAMTS13 in vascular endothelial cells and Madin-Darby canine kidney cells depends on the CUB domains and their association with lipid rafts

Abstract: ADAMTS13 biosynthesis appeared to occur mainly in hepatic stellate cells, but detection of ADAMTS13 mRNA in many other tissues suggests that vascular endothelium may also produce ADAMTS13. We showed that ADAMTS13 mRNA and protein were detectable in human umbilical vein endothelial cells, aortic endothelial cells, and endothelium-derived cell line (ECV304). ADAMTS13 in cell lysate or serum-free conditioned medium cleaved von Willebrand factor (VWF) specifically. IntroductionADAMTS13, a member of a disintegrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 56 publications
(103 reference statements)
5
94
1
Order By: Relevance
“…It is not clear why mouse ADAMTS13 did not exhibit apical polarity of secretion as previously reported with human ADAMTS13. 7 A similar pattern of substrate-dependent divergence in activity was also observed with human ADAMTS13 and its recombinant variants. Compared with normal human plasma ADAMTS13, truncated proteins AD2 and AD5, but not AD6 or the full-length AD7, exhibited higher activity against VWF73 peptides than against VWF multimers.…”
Section: Iap Retrotransposon In Mouse Adamts13 Gene 891mentioning
confidence: 54%
See 2 more Smart Citations
“…It is not clear why mouse ADAMTS13 did not exhibit apical polarity of secretion as previously reported with human ADAMTS13. 7 A similar pattern of substrate-dependent divergence in activity was also observed with human ADAMTS13 and its recombinant variants. Compared with normal human plasma ADAMTS13, truncated proteins AD2 and AD5, but not AD6 or the full-length AD7, exhibited higher activity against VWF73 peptides than against VWF multimers.…”
Section: Iap Retrotransposon In Mouse Adamts13 Gene 891mentioning
confidence: 54%
“…7 To determine whether the IAP-a variant protein was secreted with a different polarity, we transfected MDCK cells grown on Transwell filters with mouse ADAMTS13 cDNA plasmids. The results showed that 48.9% Ϯ 10.1% (n ϭ 5) of recombinant IAP-a and 48.2% Ϯ 9.6% (n ϭ 5) of recombinant mouse full-length ADAMTS13 were secreted apically (P Ͼ .5).…”
Section: Expression Of Adamts13 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CUB domain of ADAMTS13 was shown to be important for the constitutive localization of ADAMTS13 to lipid rafts [47]. However, biochemical properties of Gp140 suggest that Gp140 does not always reside in DRMs and may, instead, only transiently associate with these domains upon outside-in signaling or cross-linking (Fig.…”
Section: Evidence That Drm and Tem Components Are Required For Phosphmentioning
confidence: 99%
“…ADAMTS13 antigen is present in the plasma of patients with acquired TTP, where it appears to be in complex with auto-antibodies [12], and is absent in congenital TTP [11,13]. The cellular origin of ADAMTS13 in plasma has not been completely elucidated but the protease has been shown to be synthesized in liver stellate cells and in endothelial cells [14,15]. ADAMTS13 mRNA has been detected in a variety of tissues including the kidneys [4,16,17].…”
Section: Introductionmentioning
confidence: 99%